Does anxiety moderate the effectiveness of mirtazapine in patients with treatment-resistant depression? A secondary analysis of the MIR trial. (December 2020) - Rifkin-Zybutz, Raphael; MacNeill, Stephanie; Davies, Simon JC; Dickens, Christopher; Campbell, John; Anderson, Ian M; Chew-Graham, Carolyn A; Peters, Tim J; Lewis, Glyn; Wiles, Nicola; Kessler, David
Background: There is a lack of evidence to guide treatment of comorbid depression and anxiety. Preliminary evidence suggests mirtazapine may be effective in treating patients with both depression and anxiety symptoms. Methods: We undertook a secondary analysis of mirtazapine (MIR): a placebo-controlled trial of the addition of mirtazapine to a selective serotonin reuptake inhibitor or serotonin–norepinephrine reuptake inhibitor in treatment-resistant depression (TRD) in primary care. We subdivided participants into three groups by baseline generalized anxiety disorder score (GAD-7): severe (GAD-7 ⩾ 16), moderate (GAD-7 = 11–15), no/mild (GAD-7 ⩽ 10). We used linear regression including likelihood-ratio testing of interaction terms to assess how baseline anxiety altered the response of participants to mirtazapine as measured by 12-week GAD-7 and Beck Depression Inventory II (BDI-II) scores. Results: Baseline generalized anxiety moderated mirtazapine's effect as measured by GAD-7 ( p = 0.041) and BDI-II ( p = 0.088) at 12 weeks. Participants with severe generalized anxiety receiving mirtazapine had lower 12-week GAD-7 score (adjusted difference between means (ADM) −2.82, 95% confidence interval (CI) −0.69 to −4.95) and larger decreases in BDI-II score (ADM −6.36, 95% CI −1.60 to −10.84) than placebo. Conversely, there was no anxiolytic benefit (ADM 0.28, 95% CI −1.05 to 1.60) or antidepressant benefit (ADM −0.17, 95% CI −3.02 to 2.68) compared with placebo in those with no/mild generalized anxiety. Conclusions: These findings extend the evidence for the effectiveness of mirtazapine to reduce generalized anxiety in TRD in primary care. These results may inform targeted prescribing in depression based on concurrent anxiety symptoms, although these conclusions are constrained by the post-hoc nature of this analysis.